MONOPOLIZED MARKET KOKAND BRANCH of TASHKENT STATE TECHNICAL UNIVERSITY NAMED ISLAM KARIMOV - Javohir Komilov; Mo’ydinova Dilfuzaxon. (Ta’lim innovatsiyasi va integratsiyasi, 2024)
Annotation: The monopolized market is one of the important factors that have a negative impact on the state economy. Significant efforts are made to end monopolies worldwide. This acticle defines the monopolized market, examines the reasons for its emergence, and analyzes the work being done to combat it.